“A Dog Brings Benefits No Matter Where It’s from”: UK Residents’ Understanding of the Benefits and Risks of Importing Puppies from Romania to the UK - Zoe Belshaw; Elizabeth Youens; Michelle Lord; Rowena M. A. Packer (Animals)
The United Kingdom (UK) is a key market for puppy importation from the European Union (EU), as demand for puppies exceeds domestic supply. Many are illegally imported. Potential welfare risks to the puppies and negative impacts of these on their prospective owners are well documented, but UK residents’ perspectives on the trade are not. This study aimed to use an online survey to capture UK residents’ understanding of the benefits and risks to imported puppies of being imported from Romania for sale in the UK, and the benefits and risks of buying an imported puppy for their prospective owners. Eligible responses were collected from n = 7184 participants; 4000 randomly selected free-text comments underwent content analysis. Respondents displayed a limited understanding of the nature and range of risks potentially associated with puppy importation. Worryingly, many viewed an EU-born puppy as equivalent to one bred in the UK; others considered them as “rescued”. Synonyms used for non-endemic diseases that might be carried by the puppies varied widely, suggesting substantial confusion may exist on this topic. The UK public may underestimate the potential risks associated with buying a puppy bred in the EU, which plays into the hands of illegal puppy traders.